The Role of Life Satisfaction Enhancing Factors During the Covid-19 Pandemic - Khachatryan, Narine; Grigoryan, Ani; Hakobjanyan, Anna; Manusyan, Sona (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article presents the results of the research aimed at studying the predictive factors of life satisfaction during a pandemic in Armenia. The data was collected during the first wave of the coronavirus outbreak (May-June 2020). The results of the regression analysis showed that economic status and age, as demographic factors, were significant predictors for life satisfaction. Among personality factors, resilience, anxiety, and helping behavior significantly predetermined life satisfaction.
Keywords: pandemic; life satisfaction; subjective well-being; resilience; anxiety; mental health; fear of coronavirus; health-promoting behavior; pro-social behavior